1994
DOI: 10.1007/bf00391005
|View full text |Cite
|
Sign up to set email alerts
|

Replication of the Streptomyces plasmid pSN22 through single-stranded intermediates

Abstract: The replication of the 11 kb conjugative multicopy Streptomyces plasmid pSN22 was analyzed. Mutation and complementation analyses indicated that the minimal region essential for plasmid replication was located on a 1.9 kb fragment of pSN22, containing a transacting element encoding a replication protein and a cis-acting sequence acting as a replication origin. Southern hybridization showed that minimal replicon plasmids accumulated much more single-stranded plasmid molecules than did wild-type pSN22. Only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The regulatory gene, traR, is immediately upstream of the tra operon and is transcribed in the opposite direction (19). The promoter region also functions as an initiation site for secondstrand synthesis to convert the single-stranded intermediate from rolling-circle replication into the double-stranded form (17). Sequence analysis indicated that traR encodes a putative protein of 27 kDa.…”
mentioning
confidence: 99%
“…The regulatory gene, traR, is immediately upstream of the tra operon and is transcribed in the opposite direction (19). The promoter region also functions as an initiation site for secondstrand synthesis to convert the single-stranded intermediate from rolling-circle replication into the double-stranded form (17). Sequence analysis indicated that traR encodes a putative protein of 27 kDa.…”
mentioning
confidence: 99%
“…In pSN22, DSO (previously called ori1 ) exists in the Nae I‐ Bst EII region from nucleotide positions 7419 to 8195 [6]. Comparison of the nucleotide sequences of the DSO regions of pSN22, pIJ101, and pJV1 revealed three separate highly conserved sequences, from nucleotide positions 7660 to 7763, 7823 to 7869, and 7949 to 8033, respectively, of pSN22 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The nucleotide sequence of the putative nicking site, 5′‐CTTGGGA‐3′, was not identical to the 7‐bp consensus sequence, 5′‐CTTGATA‐3′, of the pC194 group of plasmids [10]. It is proposed that conserved region I is also essential for pSN22 replication, because a plasmid molecule lacking the Nae I‐ Sma I region (from nucleotide positions 7419 to 7778) of DSO could not replicate in S. lividans [6]. Conserved region III overlaps with the putative translation start codons of rep .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations